FORMULATION OPTIMIZATION AND EVALUATION OF TINIDAZOLE IN-SITU GEL - Payal, Yaduwanshi; Anindya, Goswami; Neelesh, Malviya (Journal of Biomedical and Pharmaceutical Research, 2021)
The study deals with formulation optimization and evaluation of tinidazole gel by using sodium alginate as gelling agent calcium chloride, sodium citrate were used as cross linking agent. The polymeric solution of drug is in solution form before it administered to the body. But after administration when it comes in contact with acidic pH it’s converted into gel form and the drug tinidazole released from the dosage form constantly and slowly. The formulation is effective for the treatment of gastric ulcer because of Helicobacter pylori. 32 full factorial design were used for the optimization of the formulation 12 trial batches were prepared and 9 factorial design batches in which 2 factor 3 level factorial design were used for the optimization. The concentration of sodium alginate, were taken in 3 level low, medium, high and the prepared formulation were evaluated.